GPs’ use and understanding of the benefits and harms of treatments for long-term conditions: a qualitative interview study - Treadwell, J; Crocker, J; Rushforth, A; Mahtani, K; Greenhalgh, P (Royal College of General Practitioners, 2021)
Background To support shared decision making and improve the management of polypharmacy, it is recommended that GPs take into account quantitative information on the benefits and harms of treatments (QIRx). Quantitative evidence shows GPs’ knowledge of this is low.